A Report on the First Workshop on Document Intelligence (DI) at NeurIPS 2019 - Motahari, Hamid; Duffy, Nigel; Bennett, Paul; Bedrax-Weiss, Tania (SigKDD Explorations, 2020)
The first workshop on Document Intelligence (DI’2019) was held on December 14, 2019 at NeurIPS 2019 conference in Vancouver, Canada. The report summarizes the workshop, with a summary of the talks, papers and posters presented, and discusses common themes, issues and open questions that came up in the workshop.